Drug-Resistant Strains in Surgical Site Infections after Abdominal Surgery: A Prospective Study - Gupta, Veenu; Kaur, Prateet; Chhina, Deepinder; Singh, Jaspal; Gupta, Rama (Journal of Gastrointestinal Infections, 2022)
Background Surgical site infection (SSI) is a common complication of abdominal surgery associated with substantial discomfort, morbidity, and cost.Objective The aim of this study was to determine the incidence, risk factors, and antimicrobial susceptibility pattern of the associated bacterial causes of SSI in patients after abdominal surgery.Methods A prospective study over a 1-year (Jan 2019–Dec 2019) period was conducted at a tertiary care institution in North India. Postoperative patients of abdominal surgeries with SSI were included in the study. Any exudate from the surgical site was collected aseptically and was processed as per standard operating procedures.Results Of 2,509 patients with abdominal surgeries included in the study, 75 (2.98%, majority, i.e., 50 males) developed SSI. Common risk factors found to be associated with the development of SSI include contaminated surgical sites, obesity, age, immunosuppression, and simultaneous infection at some other sites, with a predominance (89.3%) of gram-negative isolates. Escherichia coli was the most frequently isolated organism (45.3%), followed by Klebsiella spp. (20%), Acinetobacter spp.(10.6%), Pseudomonas spp., and Staphylococcus aureus (8% each). There was a very high (53%) prevalence of extended-spectrum β lactamase production among the E. coli and Klebsiella isolates. Additionally, 58.8% of the E. coli isolates were multidrug-resistant, whereas 73.3% of the Klebsiella isolates were exclusively drug resistant. All the S. aureus isolates were found to be methicillin-resistant.Conclusion Although the SSI rates after abdominal surgery were low, multidrug-resistant gram-negative bacteria were predominant in SSI.
Keywords: abdominal surgeries; surgical site infection; risk factors; antimicrobila susceptibility; multidrug-resistant